2021
DOI: 10.3390/microorganisms9102163
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Hybrid Diarrhoeagenic Escherichia coli Associated with Multidrug Resistance in Environmental Water, Johannesburg, South Africa

Abstract: This study was undertaken to determine the virulence and antibiotic resistance profiles of diarrhoeagenic Escherichia coli (DEC) in environmental waters of Johannesburg, South Africa. Samples were collected and cultured on selective media. An 11-plex PCR assay was used to differentiate five DEC, namely: enteroaggregative (EAEC), enterohaemorrhagic (EHEC), enteroinvasive (EIEC), enteropathogenic (EPEC) and enterotoxigenic (ETEC). The antibiotic resistance profile of isolates was determined using the VITEK®-2 au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(86 reference statements)
2
9
2
Order By: Relevance
“…Escherichia coli ( E. coli ) is an anaerobic Gram-negative, rod-shaped bacterium that belongs to the Enterobacteriaceae family found in the human guts, warm-blooded animals, cold-blooded animals, as well as in different environments [ 5 , 6 ]. It can further be found in the environment such as in water [ 7 ]. Amongst the strains are diverse pathogens that can cause variety of diseases and a majority of them are difficult to treat [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli ( E. coli ) is an anaerobic Gram-negative, rod-shaped bacterium that belongs to the Enterobacteriaceae family found in the human guts, warm-blooded animals, cold-blooded animals, as well as in different environments [ 5 , 6 ]. It can further be found in the environment such as in water [ 7 ]. Amongst the strains are diverse pathogens that can cause variety of diseases and a majority of them are difficult to treat [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these strains are also a primary cause of foodborne outbreaks in people as well as animals [ 9 ]. Human diarrhoeal outbreaks and other dangerous waterborne diseases are caused by diarrhoeagenic Escherichia coli (DEC) strains [ 10 , 11 ]. Five types of DEC reported are Enterohaemorrhagic E. coli (EHEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enteroaggregative E. coli (EAEC), and enteroinvasive E. coli (EIEC) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This conviction collapsed due to the fact that this severe outbreak was caused by a hybrid strain bearing the virulence factors of enteroaggregative E. coli and Shiga-toxin-producing E. coli simultaneously [ 16 , 17 ]. After that, many studies have shown that E. coli strains combining genetic markers belonging to different pathotypes are more frequent than previously thought [ 12 , 13 , 14 , 15 ]. Hybrid DEC are associated with more serious diseases and may frequently progress to HUS, which could be explained by producing a set of proteins involved in intestinal colonization, leading to persistent diarrhea and facilitating Stx absorption [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in techniques allowing the better understanding of the genomic and virulence mechanisms among diarrheagenic E. coli led to detecting atypical hybrid E. coli strains combining genetic markers of different pathotypes [ 12 , 13 , 14 ]. Hybrid DEC strains carrying various combinations of virulence factors have emerged worldwide and have been reported as a public health concern [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some articles included in the first and second edition of this Special Issue highlight significant progress made in this field. In particular, it concerns further advances achieved in addressing the contribution of multidrug-resistant E. coli strains to the development of intestine infection [2] and some health disorders [3,4]. Other reports provide a number of interesting insights into the mechanisms of pathogenesis by addressing the role of colicins [5] and bacterial toxins [6] during the infection process and by providing insights into various adaptation strategies [7][8][9][10].…”
mentioning
confidence: 99%